2016
DOI: 10.3390/s16122028
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Smart Air Conditioning by Sensor Development: A Review

Abstract: The study investigates the development of sensors, in particular the use of thermo-fluidic sensors and occupancy detectors, to achieve smart operation of air conditioning systems. Smart operation refers to the operation of air conditioners by the reinforcement of interaction to achieve both thermal comfort and energy efficiency. Sensors related to thermal comfort include those of temperature, humidity, and pressure and wind velocity anemometers. Improvements in their performance in the past years have been stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…Having access to this data, the smart air conditioner is able to adapt the cooling effort. Therefore, well developed devices not only can reduce the environmental impact but also enhance users' comfort [15]. In the interest of comparing the energy savings achieved with an air conditioner with other devices, the percentage of the total energy consumption has to be calculated.…”
Section: Smart Air Conditionermentioning
confidence: 99%
“…Having access to this data, the smart air conditioner is able to adapt the cooling effort. Therefore, well developed devices not only can reduce the environmental impact but also enhance users' comfort [15]. In the interest of comparing the energy savings achieved with an air conditioner with other devices, the percentage of the total energy consumption has to be calculated.…”
Section: Smart Air Conditionermentioning
confidence: 99%
“…With the development of information and communication technologies such as the computer, cloud, and Internet of Things (IoT), the machine learning technologies for image processing and voice processing have been combined with the deep learning technology and their application fields are spreading throughout the industry [1,2]. Moreover, as energy efficiency regulations are strengthened, increasing the energy efficiency of electronic appliances used in daily life becomes an important task [3,4]. Among electronic appliances in the living space, air conditioners use the most energy, and because of that numerous techniques have been studied to maximize energy efficiency while maintaining the same performance [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as energy efficiency regulations are strengthened, increasing the energy efficiency of electronic appliances used in daily life becomes an important task [3,4]. Among electronic appliances in the living space, air conditioners use the most energy, and because of that numerous techniques have been studied to maximize energy efficiency while maintaining the same performance [3,5]. To address these problems, various human body detection sensors are used to detect the presence of humans and control the airflow of the air conditioner [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review byCheng and Lee (2016) showed that the energy-savings potential of ACs improved from 11% before 2000 to 30% after 2000 owing to advancements in sensor technologies.…”
mentioning
confidence: 99%